Can We Control Carbon Dioxide? (from 1975) - Nordhaus, William D. (American Economic Review, 2019)
In recent years, the concern about the tradeoffs between economic growth and environmental quality have been paramount. To a large extent, the energy sector has been the locus of the major battles. For the most part, the concerns have been with local environmental problems such as disputes over air and water quality, nuclear accidents, and radioactive wastes. Although these problems have not been solved, it appears that as a result of considerable technical work that techniques exist (even if political will does not) to reduce most local environmental problems to a tolerable level. There remain on the agenda, however, a number of global environmental problems, and again these relate mainly to the energy sector. In particular, it appears that emissions of carbon dioxide particulate matter, and waste heat may, at some time in the future, lead to significant climatic modifications. Of these, it appears that carbon dioxide will probably be the first man-made emission to affect climate on a global scale, with a significant temperature increase by the end of the century.